Comparación entre la presencia de sintomatología depresiva en niños de 8 a 10 años con leucemia, discapacidad física y ausencia de problemas de salud física en Lima Metropolitana - Grieve Herrera, Alexandra (2015)
This research aims to compare the results between depressive symptomatology in children aged 8 to 10 years with leukemia, physical disability and absence of physical health problems. The sample consisted of 27 children aged 8-10 years, of which 6 have leukemia, 6 are physical disabled and 15 do not have any physical health problem. Children responded to the “Children’s Depresion Scale”, in which they had to point out pictures of faces that indicated their response. The results showed that 50% of children with leukemia had very low levels or absence of depressive symptomatology, whereas 33.3% of physically handicapped children and 13.3% of the children without health problems presented a depressive disorder. However, the results did not evidence a significative difference between the samples. Therefore, having a disease does not necessarily mean that a child will develop depression, since there are many factors involved in this diagnosis; however, these have not been addressed in this study. In addition, it is important to mention that a physical disability can have a negative impact on the children who have it, because of the limitations it implies and the permanency of the condition in their development.